Asymmetric decarboxylative [3 + 2] cycloaddition for the diastereo- and enantioselective synthesis of spiro[2.4]heptanes via cyclopropanation. Issue 8 (8th March 2022) - Gao, Can; Zhang, Ting; Li, Xiaoxun; Wu, Jing-De; Liu, Jitian
Abstract : A novel asymmetric [3 + 2] cycloaddition reaction of 1, 4-dipoles and nitroolefins catalysed by the cooperative action of the chiral palladium/phosphine complex and the chiral urea-tertiary amine is described. Abstract : Asymmetric cycloaddition reactions have emerged as one of the powerful and reliable strategies for the construction of enantioenriched molecules, especially those with polycyclic frameworks. Herein, we report the asymmetric decarboxylative [3 + 2] cycloaddition of γ-methylidene-δ-valerolactones with nitroolefins under the cooperative catalysis of a palladium complex and a chiral urea-tertiary amine, delivering a variety of chiral spiro[2.4]heptanes in good yields with high enantioselectivities and moderate diastereoselectivities. The mild reaction conditions, in conjunction with good functional group tolerance, provided an easy access to multisubstituted chiral spiro[2.4]heptanes bearing three contiguous stereogenic centers including an all-carbon quaternary stereocenter. Moreover, this study reports the first asymmetric decarboxylative and dearomative [3 + 2] reaction of 2-nitrobenzofurans with 1, 4-dipoles to afford complex polycyclic scaffolds. Large-scale synthesis and synthetic transformations of the product further demonstrate its synthetic utility.